2019
DOI: 10.1002/ijc.32110
|View full text |Cite
|
Sign up to set email alerts
|

Panitumumab‐based maintenance after oxaliplatin discontinuation in metastatic colorectal cancer: A retrospective analysis of two randomised trials

Abstract: Panitumumab is approved for RAS wild‐type metastatic colorectal cancer and was evaluated in Phase III (PRIME, NCT00364013) and Phase II (PEAK, NCT00819780) first‐line randomised studies. This retrospective analysis of these trials investigated efficacy and toxicity of panitumumab‐based maintenance after oxaliplatin discontinuation in RAS wild‐type patients. First‐line regimens were FOLFOX4 ± panitumumab in PRIME and mFOLFOX6 plus panitumumab or mFOLFOX6 plus bevacizumab in PEAK. Outcomes included median progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…89,90 Maintenance with panitumumab and 5-FU/LV after panitumumab plus FOLFOX showed numerical improvement in PFS and OS compared with single-agent panitumumab in the retrospective analysis of the PRIME and PEAK trials. 91 The toxicity of this combination did not increase, which was confirmed in the VALENTINO trial, in which maintaining single-agent panitumumab appeared to have shorter PFS (HR = 1.55, p = 0.011) than treatment with panitumumab combined with 5-FU/LV. 92 Cetuximab and panitumumab are both FDA-approved agents for the first-line treatment of CRC.…”
Section: The Egfr-related Pathwaymentioning
confidence: 73%
“…89,90 Maintenance with panitumumab and 5-FU/LV after panitumumab plus FOLFOX showed numerical improvement in PFS and OS compared with single-agent panitumumab in the retrospective analysis of the PRIME and PEAK trials. 91 The toxicity of this combination did not increase, which was confirmed in the VALENTINO trial, in which maintaining single-agent panitumumab appeared to have shorter PFS (HR = 1.55, p = 0.011) than treatment with panitumumab combined with 5-FU/LV. 92 Cetuximab and panitumumab are both FDA-approved agents for the first-line treatment of CRC.…”
Section: The Egfr-related Pathwaymentioning
confidence: 73%
“…However, the VALENTINO study, comparing panitumumab monotherapy or 5-FU/LV plus panitumumab after eight cycles of induction therapy with FOLFOX plus panitumumab, showed that monotherapy was inferior in terms of 10-month PFS rates [16]. Similarly, a recent retrospective analysis of the PEAK and PRIME studies showed that maintenance with panitumumab plus 5-FU/LV after 11e12 cycles of an oxaliplatin-containing regimen was well tolerated and may be associated with better outcomes than strategies not containing panitumumab [17]. Thus, anti-EGFR antibody monotherapy may not be a suitable treatment option after oxaliplatin-based induction chemotherapy regarding efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…PRIME and PEAK trials further analyzed the effects of panitumumab and fluorouracil/leucovorin (5-FU/LV) after panitumumab plus FOLFOX. The trials showed significant improvement in PFS and OS compared with panitumumab treatment alone [ 208 ]. In addition, the VALENTINO trial demonstrated synergistic effects of panitumumab with 5-FU/LV and better effects on outcome compared with treatment with panitumumab alone [ 209 ].…”
Section: Therapeutic Strategiesmentioning
confidence: 99%